Propuesta para la creación de preparaciones culinarias en base a un fermento de nísperos (Eriobotrya japónica) - Mejía Suarez, Steve Alexander (2023)
Finding recipes made based on medlar, is not very common compared to other commercially known fruits, the lack of interest and the scarce diffusion of this fruit, means that they do not know how to work it and it is only consumed naturally, because of that it is proposes promoting the use of medlars and their nutritional properties by preparing a ferment to be applied in three sauces. For the development of this research, we started from applied research with a mixed approach\; the methods used were inductive-deductive and analytical-synthetic through which the state of the art could be developed and in the analysis of the results of the field work. In addition, documentary, quasi-experimental and application research was carried out. For data collection, three instruments were used, a 12-question questionnaire which was applied in the city of Ibarra taking the population of this city as a universe, giving a total of 382 surveys and an interview script that was carried out. 5 professionals in the gastronomic area\; The result obtained reflects that the lack of preparations based on medlar is due to the ignorance of people regarding how to work this fruit, since they are unaware of its uses and there are no evidence of recipes that can be replicated, in addition an extensive list of preparations was collected. for the medlar sauce to be applied. Several wild fruits are not valued due to their ignorance and contain a number of properties and benefits that are not evident due to the lack of interest and diffusion of their consumption, after investigating in depth about the medlar, the ways of making use of it are extended. him and what techniques to apply for his transformation.